En-26 photocatalytic activity enhancement of Bi2WO6 via deposition of silver nanoparticles - Sim, Yang Jie (2015)
Current efforts are to improve the efficiency of photo-catalysis for usage in water treatment due to some major drawbacks of the photo-catalysts. For instance, the most widely used photo-catalyst TiO2 can only be activated under ultraviolet light. Thus, artificial light have to be employed which drives up operational cost. Therefore, attention have been shifted to searching for alternate photo-catalysts. Bi2WO6 is one of the potential compound as it is able to be activated by visible light to some extent. In this project, three Bi2WO6 samples were synthesized by varying DI water content. The samples are sphercal in shape. However, different DI water led to slight differences in the structure of the samples. The samples with lower DI water present flower-like structure, while the sample with highest DI water resembles a wool ball. Further modification by adding Ag nanoparticles in forming Ag-Bi2WO6 composites is conducted to enhance the photo-catalytic efficiency of these Bi2WO6 samples. The characterization tests prove that Ag is successfully deposited on the Bi2WO6 samples with no other impurities. Thereafter, photo-catalytic degradation of sulfanilamide is carried out. The experiment shows that pure Bi2WO6 samples can cause approximately 20% degradation of sulfanilamide. The efficiency doubled for the Ag-Bi2WO6 samples. Such improvement can be mainly attributed to the ability of Ag to act as active sites for e- to accumulate, thus reducing the chance of recombination of the photogenerated charges. This supports the feasibility of adding Ag nanoparticles to Bi2WO6 to increase photo-catalytic activity. The antibacterial capabilities of the samples are also conducted on E. coli (gram-negative) and S. aureus (gram-positive). Overall, Ag-Bi2WO6 samples present high efficiency of at least 80% to remove E. coli and above 90% in S. aureus removal. Even though Bi2WO6 display certain antibacterial activity under visible light, Ag is the main contributor in Ag-Bi2WO6 that inhibits bacterial activity due to its excellent disinfection effect.